Interrelationship between Personality Traits and Emotional Intelligence of Secondary Teachers in India - Ravi Kant (Institute of Advanced Engineering and Science, 2014)
Emotional intelligence is an ability to control our emotions in abnormal situations. Now it is widely accepted that emotional intelligence also a key determent for success and also in development in personality. Personality is a sum total of emotions. By taking a sample of 200 secondary school teachers an attempt has made to find out the relationship between emotional intelligence and different factors of personality of secondary school teachers. Results indicate that there is no significant difference between emotional intelligence of secondary school teachers in relation to gender and stream in which they are teaching. Further, a positive relationship found in the emotional intelligence and some of personality factors but many personality factors were negatively related to emotional intelligence of different groups of secondary school teachers but most type of relationship was not significant.DOI: http://dx.doi.org/10.11591/ijere.v3i3.6145